High-sensitivity cardiac troponin T release after a single bout of high-intensity interval exercise in experienced marathon runners - Li, F.; Yi, L.; Yan, H.; Wang, X.; Nie, J.; Zhang, H.; Fu, F. H. K.; Zang, Y.; Yang, S.; Lu, Y. (Journal of Exercise Science & Fitness, 2017)
Objective: The purpose of this study was to investigate the effects of a single bout of high-intensity interval exercise (HIIE) on high-sensitivity cardiac troponin T (hs-cTnT) release and to explore the potential influencing factors. Methods: Twenty-one experienced marathon runners completed HIIE on treadmill. Each bout of HIIE included a hard run (15.8 ± 1.3 km·h-1) at 90% vVO2max for 2 min followed by an easy run (8.8 ± 0.7 km·h-1) at 50% vVO2max for 2 min performed 23 times within 92 min. Heart rate (HR) was recorded every 2 min during HIIE. The hs-cTnT level was measured before (pre), immediately after (0 h), and at 4 and 24 h after exercise. Results: The hs-cTnT level was elevated at 0 h, peaked at 4 h, and had not returned to the baseline value at 24 h after exercise. The response of hs-cTnT at 4 h was positively related to exercise HR. Subjects with a greater increase in hs-cTnT level had a higher exercise HR under fixed exercise intensity. Conclusion: HIIE at 90% vVO2max interspersed with 50% vVO2max for recovery can elicit hs-cTnT elevation. HR is a good predictor of exercise-induced cardiac troponin (cTn) release under fixed exercise intensity. Further study should consider to correct for HR when constructing impact factors contributing to exercise-induced cTn release.